2018
DOI: 10.2147/prom.s156279
|View full text |Cite
|
Sign up to set email alerts
|

The importance of patient-reported outcomes in clinical trials and strategies for future optimization

Abstract: Patient-reported outcomes (PROs) can be included in clinical trials as primary or secondary endpoints and are increasingly recognized by regulators, clinicians, and patients as valuable tools to collect patient-centered data. PROs provide unique information on the impact of a medical condition and its treatment from the patient’s perspective; therefore, PROs can be included in clinical trials to ensure the impact of a trial intervention is comprehensively assessed. This review first discusses examples of how P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
353
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 378 publications
(361 citation statements)
references
References 65 publications
1
353
0
7
Order By: Relevance
“…Indeed, with regard to ERNs, two key drivers have been identified:, on the one hand, medical experts and scientists (because of the existing interdependence of research and care in this highly specialized field) and on the other hand patients and their families, including the patient organizations [379]. In the set-up of clinical trials, patient reported outcomes (PRO) are also increasingly gaining importance [380].…”
Section: How Can We Keep In Touch With Changes Of Marfan Syndrome?mentioning
confidence: 99%
“…Indeed, with regard to ERNs, two key drivers have been identified:, on the one hand, medical experts and scientists (because of the existing interdependence of research and care in this highly specialized field) and on the other hand patients and their families, including the patient organizations [379]. In the set-up of clinical trials, patient reported outcomes (PRO) are also increasingly gaining importance [380].…”
Section: How Can We Keep In Touch With Changes Of Marfan Syndrome?mentioning
confidence: 99%
“…However, it might be challenging to identify the correct PROMs to use in a study, to administer them at the right time, and to minimize and deal with missing data. 7,21 Many PROMs are tailored to measure the patient perspective in particular areas, for example, symptom-specific (eg, pain, fatigue, and anxiety) and disease-specific instruments that are most relevant to a patient population. In contrast, there are generic instruments that do not focus on a particular disease or symptom but aim to assess HRQOL in general, allowing comparisons between different conditions, and providing valuable data for economic evaluation…”
Section: Introductionmentioning
confidence: 99%
“…These evaluations, captured electronically or in person, in formats ranging from questionnaires to wearable devices, serve to provide a unique record of the patient's lived experience of a disease, its treatment and management, and the impact these may have on function and health‐related quality of life (HRQoL) . The inclusion of PROs as trial endpoints aims to ensure a comprehensive assessment of burden of disease and the impact of an intervention . In this way, PROs have established themselves as a central and indispensable component of the evidence evaluating medicines and can be used by clinicians, patients and policy makers to assess treatment choice, shape guidelines and enable regulatory and policy decisions based on the benefits and costs of treatment .…”
Section: Introductionmentioning
confidence: 99%
“…Reasons cited for the poor quality of PROs in some cancer clinical trials include methodological, cultural and practical issues . Choice and content of PRO measures are not always relevant to the aim of the study or may not reflect what is important to the patient . PROs are all too often dismissed as subjective in contrast to laboratory findings and as less important than survival endpoints .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation